Step
*
2
1
1
2
1
1
1
of Lemma
enumerate_wf
1. P : ℕ ⟶ 𝔹
2. n : ℤ
3. 0 < n
4. ∀n:ℕ. ∃k:ℕ. ((↑(P k)) ∧ (n ≤ k))
5. enumerate(P;n - 1) = enumerate(P;n - 1) ∈ ℕ
6. ↑(P enumerate(P;n - 1))
7. ¬(n = 0 ∈ ℤ)
8. m : ℕ
9. enumerate(P;n - 1) = m ∈ ℕ
10. ∃n:ℕ. (↑(P ((m + 1) + n)))
11. mu(λk.(P ((m + 1) + k))) ∈ ℕ
12. (↑((λk.(P ((m + 1) + k))) mu(λk.(P ((m + 1) + k)))))
∧ (∀[i:ℕ]. ¬↑((λk.(P ((m + 1) + k))) i) supposing i < mu(λk.(P ((m + 1) + k))))
⊢ (m + 1) + mu(λk.(P ((m + 1) + k))) ∈ {k:ℕ| ↑(P k)} 
BY
{ (MemTypeCD THEN Auto) }
Latex:
Latex:
1.  P  :  \mBbbN{}  {}\mrightarrow{}  \mBbbB{}
2.  n  :  \mBbbZ{}
3.  0  <  n
4.  \mforall{}n:\mBbbN{}.  \mexists{}k:\mBbbN{}.  ((\muparrow{}(P  k))  \mwedge{}  (n  \mleq{}  k))
5.  enumerate(P;n  -  1)  =  enumerate(P;n  -  1)
6.  \muparrow{}(P  enumerate(P;n  -  1))
7.  \mneg{}(n  =  0)
8.  m  :  \mBbbN{}
9.  enumerate(P;n  -  1)  =  m
10.  \mexists{}n:\mBbbN{}.  (\muparrow{}(P  ((m  +  1)  +  n)))
11.  mu(\mlambda{}k.(P  ((m  +  1)  +  k)))  \mmember{}  \mBbbN{}
12.  (\muparrow{}((\mlambda{}k.(P  ((m  +  1)  +  k)))  mu(\mlambda{}k.(P  ((m  +  1)  +  k)))))
\mwedge{}  (\mforall{}[i:\mBbbN{}].  \mneg{}\muparrow{}((\mlambda{}k.(P  ((m  +  1)  +  k)))  i)  supposing  i  <  mu(\mlambda{}k.(P  ((m  +  1)  +  k))))
\mvdash{}  (m  +  1)  +  mu(\mlambda{}k.(P  ((m  +  1)  +  k)))  \mmember{}  \{k:\mBbbN{}|  \muparrow{}(P  k)\} 
By
Latex:
(MemTypeCD  THEN  Auto)
Home
Index